2012
DOI: 10.1080/0907676x.2011.632689
|View full text |Cite
|
Sign up to set email alerts
|

The Pear Tree Project: a geographico-statistical and linguistic analysis

Abstract: The original analysis of the figures relating to the Pear Tree project (see Salway 2007) involving detailed breakdowns of the results recorded at universities in Catalonia, Ireland, Italy, Poland and Belgium, have already provided interesting, if rather limited, data relating to how film texts are perceived by subjects coning from different nations/languages/cultures. These figures have now been supplemented by results recorded in Germany, Greece, South Africa, Britain, America, Spain and France. These additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the studies conducted as part of the project activities, participants from different European countries were asked to perform the same activity with data then subjected to comparative analyses to uncover similarities and differences in the way certain tasks were performed by representatives of the languages and cultures concerned. Taylor & Mauro's (2012) Pear Tree project was carried out internationally at 11 universities in Europe (France, Germany, Great Britain, Greece, Ireland, Italy, Belgium, Poland, and Spain), the United States, and the Republic of South Africa (involving Afrikaans-speaking participants).…”
Section: Cross-national Research: Definition and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies conducted as part of the project activities, participants from different European countries were asked to perform the same activity with data then subjected to comparative analyses to uncover similarities and differences in the way certain tasks were performed by representatives of the languages and cultures concerned. Taylor & Mauro's (2012) Pear Tree project was carried out internationally at 11 universities in Europe (France, Germany, Great Britain, Greece, Ireland, Italy, Belgium, Poland, and Spain), the United States, and the Republic of South Africa (involving Afrikaans-speaking participants).…”
Section: Cross-national Research: Definition and Applicationsmentioning
confidence: 99%
“…Based on a research vehicle devised by Chafe (1980), participants were shown a short video clip without dialogue and were asked to write down what they had seen. The project was designed with the aim of enabling an intercultural comparison of the film descriptions in order to study verbalisation modalities across languages and cultures (Gronek, Gorius & Gerzymisch-Arbogast, 2012;Mazur & Kruger, 2012;Taylor & Mauro, 2012). The DTV4ALL project was a European venture designed to facilitate the provision of access services on digital television across the European Union.…”
Section: Cross-national Research: Definition and Applicationsmentioning
confidence: 99%
“…In terms of verb tense it is perhaps surprising to note that the English use the present tense more than most, whereas the Italians and the Spanish, who have a historic present tense, used it less. The discussion of the reasons behind the discrepancies that emerged has now been reported (Taylor and Mauro 2012).…”
Section: Translationmentioning
confidence: 99%